Kajian Pengembangan Terminal Penumpang Bandar Udara Sultan Babullah - Ternate - Winahyu, Sri Hapsari (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
BasU: infrastructure for passenger aircraft is passenger terminal building. The increase in the numberof passengers at airports by Sultan Babullah necessarily requires an increase in the service of passengers,namely the development of passenger terminals or through optimization of the existing infrastnicture.From the data processing, estimated passenger Babullah Sultan Ternate Airport in 2014 will amountto 643,756 people, with the number of passengers at peak hours as mam; as 202 people. VVith resultslike these, then in 2014 the passenger terminal area required by the Sultan of Ternate BabullahAirport is 2828 m2.